2017
DOI: 10.1590/0103-8478cr20150767
|View full text |Cite
|
Sign up to set email alerts
|

Stability in chromosome number and DNA content in synthetic tetraploids of Lolium multiflorum after two generations of selection

Abstract: Chromosome doubling of Italian ryegrass genotypes ( Lolium multiflorum Lam.) adapted to the brazilian edaphoclimatic conditions is an important strategy used by breeders and aims to obtain more vigorous genotypes with better forage quality and disease resistance. The effectiveness of chromosome doubling can be measured by genetic stability and fertility rates of plants over generations. However, a common problem in the polyploidization process is the regeneration of mixoploid plants that have impaired fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Previous studies with tetraploid cultivars of Italian ryegrass showed mixoploids plants can be found by the nonhomogeneous induction of polyploidy with colchicine in diploids plants. In some tissues, chromosomes cannot be duplicated and regenerated, in which the next generations could present a variable chromosomes number range from 14 to 28 (Pereira et al 2017). However, the results of this research did not demonstrate any mixoploid individual from TSC♂ × TSC♀ progenies, suggesting a good selection process during the cultivar development.…”
Section: Chromosome Countingmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous studies with tetraploid cultivars of Italian ryegrass showed mixoploids plants can be found by the nonhomogeneous induction of polyploidy with colchicine in diploids plants. In some tissues, chromosomes cannot be duplicated and regenerated, in which the next generations could present a variable chromosomes number range from 14 to 28 (Pereira et al 2017). However, the results of this research did not demonstrate any mixoploid individual from TSC♂ × TSC♀ progenies, suggesting a good selection process during the cultivar development.…”
Section: Chromosome Countingmentioning
confidence: 56%
“…The regeneration using cell culture in treatments to diploid genotypes of perennial ryegrass and cold storage produced 18 plants with albinism (problems with pigment biosynthesis) and four chimera plants, in which the nuclear DNA content ranged from triploid to pentaploid (Creemers-Molenaar et al 1992). Thus, low temperatures can act as cell division inhibitors and exhibit similar effects of antimitotics compounds (Pereira et al 2017).…”
Section: Chromosome Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow progress of induced polyploidy after early induction of the chromosome set doubling event of chromosome is the major hindrance of low success rate of polyploidy breeding. The mixoploid condition (2×, 3× and 4×) in freshly developed material and subsequent generation reduced the performance, stability and fertility of induced polyploids [90], which was regarded as a major hindrance for the commercialization of polyploidy species. However, selection of pure and stable polyploidy genotypes in advanced generation can improve the performance of the induced polyploid species.…”
Section: Factor Affecting the Success Of Induced Polyploidymentioning
confidence: 99%
“…However, selection of pure and stable polyploidy genotypes in advanced generation can improve the performance of the induced polyploid species. It was observed that selection for several generations could lead to the increased frequency of polysomic tetraploid plants in Lolium multiflorum [90]. Lolium species probably showed better results of the selection and thus was finally commercialized as polysomic tetraploid species [61].…”
Section: Factor Affecting the Success Of Induced Polyploidymentioning
confidence: 99%